Fighting Corruption in Education: What Works and Who Benefits? - Oana Borcan; Mikael Lindahl; Andreea Mitrut (Institute for the Study of Labor (IZA), 2015)
We investigate the distributional consequences of a corruption-fighting initiative in Romania targeting the endemic fraud in a high-stakes high school exit exam, which introduced CCTV monitoring of the exam and credible punishment threats for teachers and students. We find that the campaign was effective in reducing corruption and, in particular, that monitoring increased the effectiveness of the punishment threats. Estimating the heterogeneous impact for students of different poverty status we show that curbing corruption led to a worrisome score gap increase between poor and non-poor students. Consequently, the poor students have reduced chances to enter an elite university.
Keywords: I21; I24; K42; 330; corruption; high-stakes exam; bribes; monitoring and punishment